Pelatihan Pemanfaatan Mendeley sebagai Management Reference Tool pada Artikel Ilmiah Mahasiswa di Jawa Timur - Ria Zulkha Ermayda; Dwi Narullia; Muhammad (Universitas Muhammadiyah Malang, 2022)
This community service aims to train students to use the Mendeley desktop reference tool management for higher education students throughout East Java. This training is carried out to prepare students to fulfill their obligations and comply with the ethics of publications. The training was conducted online using the Zoom Meeting application, which 275 participants attended. The training was divided into three sessions. The first session presented material on introducing writing styles and the Mendeley desktop application, which was preceded by filling out a pre-test. The second session, the delivery of material on the operation and joint practice of using the Mendeley desktop ended with session 3, namely questions and answers and filling out the post-test. The results of the training and post-test provided, as many as 98 percent of the participants were able to cite and compile a bibliography automatically, while 100 percent of the participants planned to continue to use the Mendeley Desktop application for their weekly assignments and final assignments.